2003
DOI: 10.1149/1.1540156
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of O[sub 2]-N[sub 2] Effective Diffusivity in Porous Media at High Temperatures Using an Electrochemical Cell

Abstract: The effective diffusivity of O 2 -N 2 in porous media was measured at high temperatures ͑650-800°C͒ using an electrochemical concentration cell. Porous membranes having total porosity between 29 and 48 vol% were fabricated from Sr-doped LaMnO 3 ͑LSM͒ with 20 to 30 wt% carbon added as a pore former. The O 2 -N 2 effective binary diffusivity, D O 2 -N 2 eff , at 800°C increased from ϳ0.016 to ϳ0.12 cm 2 /s with increasing open porosity between 15 and 44 vol%. The D O 2 -N 2 eff exhibited a nonlinear dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 7 publications
8
82
1
Order By: Relevance
“…This is within the range of 1.5-7.8 previously published for various porous cathodes with ϳ30% porosity. 18,19 The increasing tortuosity is caused by pore coarsening. [20][21][22][23] Coarsening causes higher standard deviation in tortuosity caused by the variance in the pore size distribution.…”
Section: Electrochemical and Solid-state Letters 10 ͑12͒ B214-b217 ͑mentioning
confidence: 99%
“…This is within the range of 1.5-7.8 previously published for various porous cathodes with ϳ30% porosity. 18,19 The increasing tortuosity is caused by pore coarsening. [20][21][22][23] Coarsening causes higher standard deviation in tortuosity caused by the variance in the pore size distribution.…”
Section: Electrochemical and Solid-state Letters 10 ͑12͒ B214-b217 ͑mentioning
confidence: 99%
“…Malek and Coppens [43] studied the effects of surface roughness on Knudsen regime diffusion in porous media. Knudsen diffusion is a result of collisions of gas molecules with the pore walls, rather than intramolecular collisions, so we always consider that Knudsen diffusion and molecular diffusion compete with one another by a "resistances in series" approach [44]. Welty et al [45] presented the different types of diffusion as shown in Figure 9.…”
Section: Knudsen Diffusion In Shalementioning
confidence: 99%
“…(2) Activation polarization -that associated with the occurrence of the overall electrochemical cathodic reaction of charge transfer. The former is relatively small, as long as the cathode is thin and has sufficient porosity [14]. The latter is the dominant one, and depends upon a number of microstructural and intrinsic -fundamental, parameters.…”
Section: Executive Summarymentioning
confidence: 99%
“…Using model developed earlier [22], equation (1) and values of various parameters from the literature [15,22,231, the electrode polarization resistance can be calculated. Figure 1 shows the calculated polarization resistance as a function of grain size and neck size at 800°C for an electrode using YSZ as the ionic conductor in the composite cathode, and the following parameters: pg (YSZ grain resistivity) = 14 Q.cm, p,, (resistivity of the space charge layer) = 2,250 n.cm, pgb (grain boundary core resistivity) = 10 Llcm, h (space charge layer thickness) = 2 nm, S,b (grain boundary core thickness) = 0.4 nm, and R,,= 2 Q.cm2.…”
Section: Application Of Space Charge Model To Comdosite Cathodementioning
confidence: 99%